If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15x = 4(x + -7) + -2(x + 3) Reorder the terms: -15x = 4(-7 + x) + -2(x + 3) -15x = (-7 * 4 + x * 4) + -2(x + 3) -15x = (-28 + 4x) + -2(x + 3) Reorder the terms: -15x = -28 + 4x + -2(3 + x) -15x = -28 + 4x + (3 * -2 + x * -2) -15x = -28 + 4x + (-6 + -2x) Reorder the terms: -15x = -28 + -6 + 4x + -2x Combine like terms: -28 + -6 = -34 -15x = -34 + 4x + -2x Combine like terms: 4x + -2x = 2x -15x = -34 + 2x Solving -15x = -34 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -15x + -2x = -34 + 2x + -2x Combine like terms: -15x + -2x = -17x -17x = -34 + 2x + -2x Combine like terms: 2x + -2x = 0 -17x = -34 + 0 -17x = -34 Divide each side by '-17'. x = 2 Simplifying x = 2
| 14x+7y=-9 | | =-16t^2+96t+1152 | | (-p-2)(p+3)= | | 268000000000=6x | | 2x+10=x+93 | | 2v^2=180 | | -3(x+6)-44=1-48 | | 11x+13=23 | | 3x-4y=-22 | | 2(y+6)=y+3+2y | | x(9x+1)=4x^2-31x+64 | | -8-3=6x+7-5x | | 2b+b+18=7b | | 4de+7df-7d+2=2e-9 | | (3x+7)-(x-4)= | | 4n^2-15n-25=0 | | 7(n-3)=2n-6 | | 20.00-1.45x=1.15 | | -16t^2+128+144=0 | | 3(x+1)+x=4x+10 | | 0.23x+2.34=6.25 | | 3a+6=-a-8 | | 0.23+2.34x=6.25 | | d-2=-2 | | 7e+12=4c+78 | | 4x+3x+1-3x-7+x= | | x-1=4(x+2)-5(x+1) | | x-1=4(x+2)-5 | | 6c+3= | | 3e^5x-2=3 | | -3x-5(4x+8)=-17 | | 2(x-3)=5(x+2)-1 |